Exploring the Diversity and Dehydration Performance of New Mixed Tutton Salts (K2V1−xM’x(SO4)2(H2O)6, Where M’ = Co, Ni, Cu, and Zn) as Thermochemical Heat Storage Materials - João G. de Oliveira Neto; Jacivan V. Marques; Jayson C. dos Santos; Adenilson O. dos Santos; Rossano Lang (Physchem)
Tutton salts form an isomorphic crystallographic family that has been intensively investigated in recent decades due to their attractive thermal and optical properties. In this work, we report four mixed Tutton crystals (obtained by the slow solvent evaporation method) with novel chemical compositions based on K2V1−xM’x(SO4)2(H2O)6, where M’ represents Co, Ni, Cu, and Zn, aiming at thermochemical energy storage applications. Their structural and thermal properties were correlated with theoretical studies. The crystal structures were solved by powder X-ray diffraction using the Rietveld method with similar compounds. All of the samples crystallized in monoclinic symmetry with the P21/a-space group. A detailed study of the intermolecular interactions based on Hirshfeld surfaces and 2D fingerprint mappings showed that the main interactions arise from hydrogen bonds (H∙∙∙O/O∙∙∙H) and dipole–ion (K∙∙∙O/O∙∙∙K). On the other hand, free space percentages in the unit cells determined by electron density isosurfaces presented low values ranging from 0.53 (V–Ni) to 0.81% (V–Cu). The thermochemical findings from thermogravimetry, a differential thermal analysis, and differential scanning calorimetry indicate that K2V0.47Ni0.53(SO4)2(H2O)6 salt is the most promising among mixed salts (K2V1−xM’x(SO4)2(H2O)6) for heat storage potential, achieving a low dehydration temperature (≈85 °C), high dehydration enthalpy (≈360 kJ/mol), and high energy storage density (≈1.84 GJ/m3).